2016
DOI: 10.3390/nu8080498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Fat Dietary Intake during Maternal Gestation on Offspring Ovarian Health in a Pig Model

Abstract: Excessive fat intake is a global health concern as women of childbearing age increasingly ingest a high fat diet. We therefore determined the association of a maternal high fat diet in pregnancy with offspring ovarian health during the gestation and postnatal female offspring in pig a model. Thirty-two Yorkshire gilts with similar bodyweights mated at the third estrus were randomly assigned to two nutrition levels of either a control (CON, crude fat: 7.27%) or a high fat diet (HFD, crude fat: 11.78%). Ovary sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Weaning weight is a key indicator of the reproductive performance of gilts, and is important in controlling their economic efficiency. Strong evidence from animal studies indicates that maternal manipulations could result in changes in the growth rates of offspring [23]. In the current study, a greater weaning weight was noticed after Tau supplementation, accompanied by an increased average daily weight gain, indicating that maternal Tau supplementation improved the growth rate of offspring.…”
Section: Discussionsupporting
confidence: 64%
“…Weaning weight is a key indicator of the reproductive performance of gilts, and is important in controlling their economic efficiency. Strong evidence from animal studies indicates that maternal manipulations could result in changes in the growth rates of offspring [23]. In the current study, a greater weaning weight was noticed after Tau supplementation, accompanied by an increased average daily weight gain, indicating that maternal Tau supplementation improved the growth rate of offspring.…”
Section: Discussionsupporting
confidence: 64%
“…Briefly, MDA content were measured based on the thiobarbituric acid (TBA) method. The activities of T-AOC, GPx, T-SOD, and VE were assayed as described by Xu et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…During pig growth, the excessive development of adipose tissue leads to an excessive accumulation of lipids, which affects the carcass quality of pigs. Overweight pigs show low lean meat rates, low feed conversion rates, and slow growth [56] , while overweight sows may experience dystocia and postpartum disease [57] . Numerous studies have shown that pigs have many similarities with humans in anatomical structure, physiological metabolism, and disease mechanisms [58,59] .…”
Section: Discussionmentioning
confidence: 99%